Awareness about Orthodontists' Role in Treating Osa and Mouth Breathing among Otolaryngologists - Anuj D. Patel; Ajay K. Kubavat; Khyati V. Patel; Vishwa Sejani; Priyal Bhavsar; Riddhi Patel (Wolters Kluwer Medknow Publications, 2024)
Background: Orthodontic correction of dentofacial abnormalities is a crucial component of oral health because it enhances overall oral health-related quality of life, optimal function, periodontal health, and aesthetics. This study sought to determine whether otolaryngologists recommend patients to orthodontists, whether they are adequately knowledgeable about the fundamentals of orthodontics, and whether they check for orthodontic problems in their patients. Materials and Method: We conducted a survey study of otolaryngologists in Gujarat, India. Questionnaires were completed by 47 out of 60 otolaryngologists (response rate 78%). Results: In the assessment of the mouth breathers, a very low frequency of "always" examining the extra-oral features (18%) was found. Reasons otolaryngologists referred patients to orthodontists varied from mouth breathing 48% (23/47) to face or teeth asymmetry 87% (41/47). In the multivariable analyses for the effect of gender, work sector, or years of experience in the decision for orthodontic referral, we could not identify any significant predictors. A low frequency of awareness of orthodontists' role in obstructive sleep apnoea, 48% (23/47) was found. Conclusion: In conclusion, the survey of otolaryngologists in Gujarat, India, revealed areas for improvement in awareness and practices related to orthodontic issues, particularly in cases of mouth breathing. The study highlighted a low frequency of examination of extraoral features and variability in referral patterns, emphasizing potential gaps in knowledge. Additionally, a low awareness of orthodontists' role in treating obstructive sleep apnea was identified. Targeted educational interventions are recommended to enhance interdisciplinary communication and collaboration between otolaryngologists and orthodontists, ultimately fostering a more comprehensive approach to patient care for individuals with dentofacial deformities in Gujarat and potentially influencing practices on a broader scale.